Effect of pyrethroid resistance on the efficacy of entomopathogenic nematodes for the control of Listronotus maculicollis (Coleoptera: Curculionidae) - Albrecht M. Koppenhöfer; Ana Luiza Sousa; Olga S. Kostromytska; Shaohui Wu (Biological Control)
Entomopathogenic nematodes can provide effective control of annual bluegrass weevil, Listronotus maculicollis, larvae, a major golf course turfgrass pest in eastern North America. The nematodes could be particularly useful for the control of insecticide-resistant weevil populations as resistance is a wide-spread problem with this pest. However, the resistance mechanism that appears to be primarily responsible for resistance in the weevil, enhanced enzymatic detoxification, may have the potential to deactivate compounds produced by the nematodes’ symbiotic bacteria that play important roles in the infection process. We compared the efficacy of several nematode species for the management of weevil larvae in populations with different insecticide resistance levels. The resistance level in weevil populations was defined based on the resistance ratio (RR50) of the pyrethroid insecticide bifenthrin. In greenhouse experiments, reduced nematode efficacy, particularly of the species Steinernema feltiae and S. carpocapsae, was already observed at moderate resistance levels (RR50 55–76) with reduction in efficacy of 20–32%. However, in field experiment efficacy was reduced only against a highly resistant weevil population (RR50 343) with a reduction of control by 16–20% for S. carpocapsae. Steinernema riobrave efficacy was not affected by insecticide resistance but was generally lower than S. carpocapsae efficacy. As most ABW populations are either not affected by resistance or have levels of resistance at which nematode efficacy is not reduced, entomopathogenic nematodes remain a useful tool for annual bluegrass weevil management and delaying insecticide resistance development.